Modified soft tissue release procedure in idiopathic congenital talipes equinovarus - Kumar Sharma, Arvind; Sharma, Vijai Prakash; Kumar Gupta, Anil; Kumar, Dileep (International Journal of Medical Research and Review, 2015)
Introduction: Initial treatment of clubfoot is non operative usually, but cases which prove to be resistant require surgical treatment. The most commonly used posteromedial incisions have been reported to have complications like skin sloughing, dehiscence, infection, limitation of full correction, hypertrophic scar and recurrence. Thus the treatment is shifting towards less aggressive surgeries. The aim of the study is to evaluate the result of a “modified soft tissue release procedure” through a single posterior incision for the correction of the idiopathic clubfoot. Materials and Methods: We conducted a prospective therapeutic study reviewing patients with idiopathic congenital clubfoot resistant to conservative management in our institution between August 2013 and July 2014. Surgical management was given by modified soft tissue release procedure. Pre and post treatment clinical, podogrammical, and radiological assessments were done. Results: A total of 82 clubfeet were reviewed. Surgical correction observed in the feet was clinically significant as per Pirani scoring, foot bimalleolar angle and talocalcaneal angle lateral view and talocalcaneal index. Improvement was clinically not significant as per talocalcaneal angle in anteroposterior view. Complications included postoperative pyrexia, pain and stiffness and superficial wound infection, 1 foot of treatment failure and 2 feet of residual deformity in the follow up period. Final clinical outcome revealed excellent and good result in 85.36% cases by this technique. Conclusion: The present study concludes that the procedure is effective in treating the deformity. The results are equivalent while complications are lesser compared to more aggressive surgeries. FBM angle is a simple method for assessment of correction.